Modular Robots for Minimally Invasive Surgery - Vilchis - González, A. H.; Ávila - Vilchis, J. C.; Estrada - Flores, R. G.; Martínez - Méndez, R.; Portillo - Rodríguez, O.; Romero - Huertas, M. (Revista Mexicana de Ingenieria Biomedica, 2014)
This article concerns the aspects that have to be taken into account for the mechanical design of modular robots to be used as a surgical tool in MIS (Minimally Invasive Surgery) interventions. For this purpose, several works concerning modular, reconfigurable and auto-reconfigurable robots are presented. Materials and surgical devices that are used for MIS are taken into account as a reference for modular and reconfigurable robots design considering regulations on medical devices and technology. The information presented in this document is oriented to abdominal ablations in laparoscopic interventions.